Qualitative analysis of biochemicals and proximate determination of saponin in different parts of Donax grandis plant extracts - Mohd Hassan, Husna Hawa; Mohd Daud, Jamaluddin; Hashim, Ridzwan; Bakhtiar, M. Taher (2010)
Bemban (Donax grandis) is a family of Marantaceae. Synonym as D. canniformis or Clinogyne grandis. It is widely distributed in Malaysia, Thailand, Singapore, Brunei, Filipina, Papua New Guinea and in other South East Asia region. It has a hollow stem like bamboos with branching at each segment. It is distributed throughout the jungle along the river and usually found in the wet places in the secondary forest and bamboo thicket. It can be propagated by seed and easily by rhizome. Although the active compound properties of these plant have not been fully documented but from the previous phytochemicals screening test, saponins are known as the main active compounds found in this plant.